Trifocal Intraocular Lens Implantation to Treat Visual Demands in Mongolian Patients - Gunchin-Ish, Narangarav; Erdenebaatar, Tumenjargal; Davaatseren, Uranchimeg (Central Asian Journal of Medical Sciences, 2022)
Objective: Intraocular lens (IOL) implants are artificial lenses which helps to clear up the vision after cataract surgery. In this work, we aimed to compare the monofocal and trifocal IOL implantation during phacoemulsification. Methods: 60 eyes of 60 patients were divided into 2 equal groups. Postoperative astigmatism and UCVA were measured and compared during week 1, week 2 and month. Results: The mean preoperative UCVA was 6.83 ± 4.61 in the monofocal IOL group, and 17.5 ± 17.55 in the trifocal IOL group. At the first week: The mean postoperative UCVA at one week was 35.46 ± 19.45 and 58.64 ± 20.77, in each group respectively. The mean postoperative BCVA in the first week was 42.71 ± 20.63 and 65.91 ± 20.85, in each group respectively. The mean postoperative UCVA at 1 month was 46.57 ± 24.37 and 76.36 ± 23.61, in each group, while BCVA was 63.14 ± 24.94 and 89.54 ± 14.63. There was a highly significant statistical difference between the result of UCVA preoperative and the results of UCVA at the early and last postoperative follow up. Conclusion: From our results, it is evident that post-operative near UCVA and BCVA was statistically significant at monofocal and trifocal groups.